Impacts of climate change on coral reefs and the marine environment - Marcia Creary (UN Chronicle, 2013)
It is estimated that 70 per cent of the Earth’s surface area is made up of oceans,1 the most productive habitat, comprising 75 per cent of all known species. This unique environment, which remains generally unexplored and hidden from the world, plays an important role in regulating global temperature and is the primary producer of oxygen. Coral reefs, which comprise only about 0.5 per cent of the ocean floor, are complex three-dimensional structures built up over thousands of years as a result of the deposition of calcium carbonate skeletons of the reef building coral species. These reefs are often referred to as the “rainforest of the sea”. This allegory underestimates the complexity of coral reefs, which have a greater diversity of animal and plant life than rainforests, circulate nutrients through the intricate food web and provide food at all levels of the food chain.